Climatological Madden-Julian Oscillation during boreal spring leads to abrupt Australian monsoon retreat and Asian monsoon onsets - Bin Wang; Lun Dai; Tat Fan Cheng; Sun-Seon Lee; Tianyi Wang; Chunhan Jin (npj Climate and Atmospheric Science, 2024)
Abstract Abrupt monsoon onsets/retreats are indispensable targets for climate prediction and future projection, but the origins of their abruptness remain elusive. This study establishes the existence of three climatological Madden-Julian Oscillation (CMJO) episodes contributing to the rapid Australian summer monsoon retreat in mid-March, the South China Sea (or East Asian) summer monsoon onset in mid-May, and the Indian summer monsoon onset in early June. The CMJO displays a dynamically coherent convection-circulation structure resembling its transitionary counterpart, demonstrating its robustness as a convectively coupled circulation system and the tendency of the transient MJOs’ phase-lock to the annual cycle. The CMJO is inactive during the boreal winter due to destructive year-to-year modulations of El Niño-Southern Oscillation. We hypothesize that the interaction between atmospheric internal variability (MJO) and the insolation-forced slow annual cycle generates the sudden monsoon withdrawal/onset during the boreal spring. Understanding the factors determining the timing and location of the MJO’s phase-locking and its variability is vital for monsoon forecasting and climate projection.